Tourism Types and Main Views - Shomirzayeva Nasiba Hoshimovna; Omonov Jahongir Vohidjon O’g’li; Maxkambayeva Shaxrizoda Xusan Qizi (Genius Journals, 2023)
This article describes the increasingly developing field of tourism and its main directions, forms and types. It was also mentioned about transport services, as they are at the level of demand of tourism zones.
Keywords: tourism; swimming tourism; railway; outdoor tourism